ESPEN guideline on Clinical Nutrition in inflammatory bowel disease - Bischoff, Stephan C; Bager, Palle; Escher, Johanna; Forbes, Alastair; Hébuterne, Xavier; Hvas, Christian Lodberg; Joly, Francisca; Klek, Stansilaw; Krznaric, Zeljko; Ockenga, Johann; Schneider, Stéphane; Shamir, Raanan; et al. (Elsevier BV, 2023)
The present guideline is an update and extension of the ESPEN scientific guideline on Clinical Nutrition in Inflammatory Bowel Disease published first in 2017. The guideline has been rearranged according to the ESPEN practical guideline on Clinical Nutrition in Inflammatory Bowel Disease published in 2020. All recommendations have been checked and, if needed, revised based on new literature, before they underwent the ESPEN consensus procedure. Moreover, a new chapter on microbiota modulation as a new option in IBD treatment has been added. The number of recommendations has been increased to 71 recommendations in the guideline update. The guideline is aimed at professionals working in clinical practice, either in hospitals or in outpatient medicine, and treating patients with IBD. General aspects of care in patients with IBD, and speciﬁc aspects during active disease and in remission are addressed. All recommendations are equipped with evidence grades, consensus rates, short commentaries and links to cited literature.
Keywords: Crohn's disease; Ulcerative colitis; Malnutrition; Obesity; Microbiota